Perlindungan Hukum Bagi Konsumen Muslim Terhadap Produk Minuman Susu “Binggrae” Berlabel Halal Korea Muslim Federation (KMF) - R A Ratna Juwita Dewi Saraswati; Anne Gunawati; Dede Agus (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Not a few South Korean processed food products that have been exported to Indonesia have not yet received a halal certificate from the MUI and/or BPJPH, but in South Korea, they have received a halal certificate from KMF, for example, the Binggrae milk drink. Based on the data, the Korea Muslim Federation (KMF) has not been included as an Overseas Halal Certification Agency (LSHLN) approved by the MUI and/or has not collaborated with BPJPH. Based on this background, it is necessary to study how the legal protection is given to Muslim consumers and what are the legal consequences arising from the inclusion of the foreign halal label. The research method used is normative juridical with the Statute Approach and Case Approach. The data used is secondary data obtained through document studies supported by primary data obtained through interviews. The collected legal materials were analyzed descriptively and qualitatively. From the results of the study, it can be concluded that legal protection for Muslim consumers against imported beverage products labeled as halal